The Effect of Learning Strategies According to O’Malley and Chamot On The Learning Outcomes of Arabic Students : تأثير استراتيجيات تعلم الطلاب عند أومالي وتشاموت في نتائج تعلم اللغة العربية - Fitriah, Feni; Zunairoh, Yuyun; Khamidah, Nur (Program Studi Pendidikan Bahasa Arab, 2023)
Arabic is often considered difficult by most students therefore an appropiate strategy is needed so that students do not find it difficult. In this case, the student learning strategy is one of components that must be considered carrefully by the teacher in improving student’s Arabic learning outcomes. Student learning strategies according to O’Malley and Chamot are divided in to 3 categories, namely metacognitive, cognitive, and affective social. The purpose of this research is to find out what strategies are used by student in learning, and the influence the student learning strategies on student learning outcomes of MAN 5 Kediri. This study used a quantitative method with an ex-post facto design. The population of this study was 230 students. While the number of samples is this study were 58 students. Sampling was determined by means of Random Sampling. The results of this study reveated that the learning strategies that were mostly used by students were cognitive strategies with an average score of 57,28. While student learning outcomes belong to the medium category. The effect of metacognitive learning strategies on learning outcomes was 4,8%, the effect of cognitive learning strategies on learning outcomes was 8,3%, and the effect of affective social learning strategies on learning outcomes was 7.1%.